(untitled) (Clinics, 2013)
OBJECTIVE: Successful revascularization of chronic total occlusions has been associated with improved left ventricular systolic function, reduced anginal symptoms, increased exercise capacity, and increased survival. This study was conducted to determine the impact of revascularization in chronic total occlusion on left ventricular function using novel echocardiographic techniques. METHODS: A total of 129 patients with chronic total occlusion who underwent revascularization between April 2011 and November 2012 were included in this study. Echocardiographic assessments with two-dimensional speckle tracking echocardiography and real-time three-dimensional echocardiography were performed before the procedure and one month after the procedure. The left ventricular ejection fraction, left ventricular volumes, and three-dimensional systolic dyssynchrony index were quantified. RESULTS: An immediate procedural success was obtained in 118 patients (91.5%). There were no acute or subacute stent thromboses during follow-up. The mean left ventricular ejection fraction significantly increased (p